Pengaruh Struktur Modal, Profitabilitas, dan Ukuran Perusahaan terhadap Nilai Perusahaan Dimoderasi oleh Kepemilikan Manajerial (Studi Kasus pada Perusahaan Sektor Barang Konsumen Primer yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Nurhidayah, Triana Dewi; Mardani, Ronny Malavia; Mustapita, Arini Fitria (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to examine the influence of capital structure, profitability, company size on company value which is moderated by managerial ownership. The population in this research is primary consumer goods sector companies listed on the Indonesia Stock Exchange (BEI) in the period 2020 to 2022. Using the purposive sampling method, a total sample of 78 primary consumer goods sector companies was obtained, so the total observations in this research were 234 observations. The type of data used in this research is secondary data. The Moderated Regression Analysis (MRA) analysis technique is used to test the interaction of independent variables and moderating variables to see whether they have an effect on dependent variable. The results of this research show that capital structure as measured by DER has a significant influence on company value, profitability as measured by ROA has no effect on company value, company size has no effect on company value, managerial ownership is able to moderate and strengthen the influence of capital structure on company value, Managerial ownership is able to moderate and strengthen the influence of profitability on company value, while managerial ownership is not able to moderate the influence of company size on company value. Keywords: Capital structure, profitability, company size, managerial ownership, company value